A settant’anni di Les orientations présentes de la pensée religieuse di Jean Daniélou (1946-2016) Un articolo programmatico che segnò un’epoca teologica - Bravo Pereira, Marcelo (Alpha Omega, 2016)
Summary: Seventy years after the publication of Jean Daniélou’s Les orientations présentes de la pensée religieuse, (1946), an article considered to be foundational for the Nouvelle théologie, its basic themes, which have become key themes of the ressourcement of Catholic theology and which exercised a decisive influence upon the Second Vatican Council, are put forward once more. These key themes are the return to the sources, philosophical influences (those of contemporary thinking) and contact with real life. The aim of Daniélou’s article is to recover the demands of the spirit of Christianity in the face of modernity, without falling into the errors of modernism.Key words: Jean Daniélou, Nouvelle théologie, modernism, ressourcement, Second Vatican Council